2016
DOI: 10.9734/bjmmr/2016/23131
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice (KAP) Regarding Osteoporosis among General Population in Saudi Arabia

Abstract: Background:Osteoporosis is a disease characterized by low bone mass and micro-architectural deterioration of bone tissue. The prevalence of osteoporosis among Saudi population was estimated at 34% in a review of the published articles up to 2011. The etiology for this high prevalence among Saudis is multi-factorial and possible causes include: lifestyle malpractices, vitamin-D deficiency and genetic factors. Aim: To evaluate knowledge and perceptions of causes and prevention of osteoporosis among general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…It is important to highlight that 83.8% or 315 participants reported having heard about OP, which is in accordance with another study in Saudi Arabia [ 19 ]. Furthermore, the knowledge difference between females and males was significant for some questions and not significant for others.…”
Section: Discussionsupporting
confidence: 88%
“…It is important to highlight that 83.8% or 315 participants reported having heard about OP, which is in accordance with another study in Saudi Arabia [ 19 ]. Furthermore, the knowledge difference between females and males was significant for some questions and not significant for others.…”
Section: Discussionsupporting
confidence: 88%
“…Another study claimed that some young adults chose not to be active even though they were quite active during their adolescents' phase (49). Therefore, a lower risk of getting osteoporosis could be achieved by avoiding sedentary lifestyle and be more active by exercising every day (50).…”
Section: Practice Of Participants Regarding Osteoporosismentioning
confidence: 99%
“…Females above the age of 40 had higher scores in all of the four OKAT subscales. A national cross-sectional study in Saudi Arabia in the year 2016[ 16 ] had a similar result, especially in the 51–65 year age group. Similarly, in a study done in Pakistan in 2006[ 26 ] revealed that younger females had poor knowledge compared to older females.…”
Section: Discussionmentioning
confidence: 66%
“…Also, participants above 51 years old had more correct answers regarding osteoporosis than those aged 15 to 35 years. [ 16 ] In Riyadh, two studies showed that there is poor application of preventive measures for osteoporosis by the Saudi females. [ 17 18 ]…”
Section: Introductionmentioning
confidence: 99%